Autophagy protects auditory hair cells against neomycin-induced damage. Issue 11 (2nd November 2017) - He, Zuhong; Guo, Lingna; Shu, Yilai; Fang, Qiaojun; Zhou, Han; Liu, Yongze; Liu, Dingding; Lu, Ling; Zhang, Xiaoli; Ding, Xiaoqiong; Liu, Dong; Tang, Mingliang; et al.
ABSTRACT: Aminoglycosides are toxic to sensory hair cells (HCs). Macroautophagy/autophagy is an essential and highly conserved self-digestion pathway that plays important roles in the maintenance of cellular function and viability under stress. However, the role of autophagy in aminoglycoside-induced HC injury is unknown. Here, we first found that autophagy activity was significantly increased, including enhanced autophagosome-lysosome fusion, in both cochlear HCs and HEI-OC-1 cells after neomycin or gentamicin injury, suggesting that autophagy might be correlated with aminoglycoside-induced cell death. We then used rapamycin, an autophagy activator, to increase the autophagy activity and found that the ROS levels, apoptosis, and cell death were significantly decreased after neomycin or gentamicin injury. In contrast, treatment with the autophagy inhibitor 3-methyladenine (3-MA) or knockdown of autophagy-related (ATG) proteins resulted in reduced autophagy activity and significantly increased ROS levels, apoptosis, and cell death after neomycin or gentamicin injury. Finally, after neomycin injury, the antioxidant N-acetylcysteine could successfully prevent the increased apoptosis and HC loss induced by 3-MA treatment or ATG knockdown, suggesting that autophagy protects against neomycin-induced HC damage by inhibiting oxidative stress. We also found that the dysfunctional mitochondria were not eliminated by selective autophagy (mitophagy) in HEI-OC-1 cells after neomycin treatment, suggesting that autophagy might not directly target the damaged mitochondria for degradation. This study demonstrates that moderate ROS levels can promote autophagy to recycle damaged cellular constituents and maintain cellular homeostasis, while the induction of autophagy can inhibit apoptosis and protect the HCs by suppressing ROS accumulation after aminoglycoside injury.